Why Do Prices Differ Across Stores? Differential Competition Environments and Their Price Impacts - Gordon Jochem Klein; Ralph Bernd Siebert (CESifo GmbH, 2024)
Our study provides empirical insights into the extent to which differential market demographics and differential competition environments affect product prices. Using big data, we find that price variations are caused mainly by differential competitive environments. More specifically, we find that Brand Competition Within Stores exerts the largest downward pressure on prices. A 10 percent increase in the number of brands reduces prices by about 10 percent. Product Competition Within Stores exerts the second-largest price effect, followed by Store Competition Within Local Markets. Moreover, retailers operating multiple stores in a local market coordinate prices to attenuate competitive downward pressure on prices.
Keywords: D40; D90; L10; L20; M20; 330; anti-inflammatory drugs; competition; market determinants; price effects; pain killers